2007
DOI: 10.1080/14786410500528478
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the essential oil ofSalvia officinalisL. from various European countries

Abstract: Variations in the essential oil composition of Salvia officinalis L. growing in Estonia and in other European countries were determined. The oils were obtained in yields of 2.2-24.8 mL kg(-1). In three samples, the content of essential oil did not conform to the EP standard (10 mL kg(-1)). Variations in the essential oil composition of sage were studied using capillary gas chromatographic methods. A total of 40 components were identified. The principal components in the sage oils were 1,8-cineole, camphor, alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(103 citation statements)
references
References 14 publications
8
87
0
8
Order By: Relevance
“…Eucalyptus globulus essential oil has been tested for its acaricidal effect against other mites [34]. Oil from Eucalyptus globulus proved to be toxic to the mites in a separate study that tested the toxic effect of the essential oil from the same species of eucalyptus against Dermanyssus gallinae [35]. The present study confirmed E. globulus to be toxic to Sarcoptes scabiei var.…”
Section: Discussionsupporting
confidence: 53%
“…Eucalyptus globulus essential oil has been tested for its acaricidal effect against other mites [34]. Oil from Eucalyptus globulus proved to be toxic to the mites in a separate study that tested the toxic effect of the essential oil from the same species of eucalyptus against Dermanyssus gallinae [35]. The present study confirmed E. globulus to be toxic to Sarcoptes scabiei var.…”
Section: Discussionsupporting
confidence: 53%
“…For instance, Scottish oil was found to have the highest content of camphor, borneol and bornyl acetate, whereas Greek oil was rich in 1,8-cineole and the monoterpenes α-pinene, camphene, β-pinene and myrcene. [28] On the other hand, the same taxon, even growing in the same country but in diff erent environmental conditions, can exhibit diff erent compositions. For example, some correlations were established between the amount of linalool in the essential oil of Thymus mastichina subsp.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Tıbbi adaçayında tuyonların (özellikle de α-tuyonun) insanlarda toksik etkisi olduğu rapor edilmiş olmakla birlikte (Höld et al, 2000), iyi kalitede tıbbi adaçayı yağının olabildiğince yüksek oranlarda α+β-tuyon (> %50) ve olabildiğince düşük oranda kafur (< %20) içermesi gerektiği bildirilmektedir (Raal et al, 2007). Ticari değeri yüksek tibbi adaçayında en kaliteli yapraklar; gümüşi renkte olan, %1.5'ten daha fazla uçucu yağ içeren, uçucu yağında α-/β-thujonları yüksek ve kafuru (kamfor) düşük olanlardır (Putievski et al, 1986a, b;1992).…”
Section: Populasyonundan Geliştirilen Klonların Verim Veunclassified